ELIZABETH AND THE GREAT FOREST (SERIES 1) ELIZABETH AND THE STRANGE ISLAND (SERIES 2) - Bernadeth Febyola Linando; Budi Darma (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
Children literature is one way to deliver important moral values to children all over the world. Therefore, I made Elizabeth and The Great Forest (Series 1) and Elizabeth and The Strange Island (Series 2) as my creative work for the final project. In those two books, I want to bring up some issues which are; technology cannot replace direct interaction between people, fears are not supposed to be avoided but to be faced, and mother-daughter relationship is the most important relationship. The first book will focus on technology that damages a girl’s social life and a girl’s bravery in overcoming her own fears. The second book will focus on mother-daughter relationship with sub-theme: overcoming the characters’ own fears. Through the girl’s journeys, she will finally realize that technology cannot replace human interaction, people need to overcome their own fears, and mother-daughter relationship is the most important relationship ever in her life.